Ludwig's angina: A case report and review of management - Sasikala Balasubramanian; P Elavenil; S Shanmugasundaram; J Himarani; V B Krishnakumar Raja (Wolters Kluwer Medknow Publications, 2014)
Space infection in the Oral and Maxillofacial region is common from odontogenic origin especially in the immunocompromised patients. Ludwig's angina which is relatively uncommon remains a potentially life-threatening condition due to the risk of impending airway obstruction. Thus, because of its invasive nature, early identification and management of Ludwig's angina is extremely important.